2015
DOI: 10.4236/jss.2015.36020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gender and Governance of Value Chain-Based Systems on Rice and Vegetable Crops in Southern Benin and Mali

Abstract: This present study analyses gender and governance in the rice and vegetable-based value chain systems in 3 lowlands of southern Benin and 2 lowlands in Southern Mali. A sample of 243 farmers, 1 modern processing unit, 18 traditional processors, 76 traders and 8 national institutions were interviewed in Benin and Mali. Descriptive statistics and Harvard analytical framework were used for the analysis of governance and gender respectively in the value chains. The majority of farmers have access to the use of lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Use of improved varieties was more popular at Tsanyawa, Albasu, Minjibir, and Matazu (Table 3). Our interviews and FGD confirmed that the use of improved cowpea varieties by farmers was low and adoption of improved varieties was mostly in areas with substantial contacts with projects like IITA programmes, and recently concluded USAIDcommissioned cowpea up-scaling project in some northern Nigerian states of Kano, Katsina and Sokoto (Adetonah et al, 2016;ICRISAT, 2017b). Some farmers said improved cowpea varieties were not used by them because they do not grow well in intercrops and they were more interested in planting cowpea as an intercrop.…”
Section: Use Of Improved Cowpea Varieties Among Smallholder Farmers I...supporting
confidence: 62%
“…Use of improved varieties was more popular at Tsanyawa, Albasu, Minjibir, and Matazu (Table 3). Our interviews and FGD confirmed that the use of improved cowpea varieties by farmers was low and adoption of improved varieties was mostly in areas with substantial contacts with projects like IITA programmes, and recently concluded USAIDcommissioned cowpea up-scaling project in some northern Nigerian states of Kano, Katsina and Sokoto (Adetonah et al, 2016;ICRISAT, 2017b). Some farmers said improved cowpea varieties were not used by them because they do not grow well in intercrops and they were more interested in planting cowpea as an intercrop.…”
Section: Use Of Improved Cowpea Varieties Among Smallholder Farmers I...supporting
confidence: 62%
“…The effect of the different factors (variables) on the use of improved rice varieties was examined using a generalized linear xed effect (all factors were xed) model of binomial family. The model containing the twenty-seven (27) explanatory variables was rst establish and the variance in ation factor (VIF) was examined for each variable in order to measure the collinearity. According to Hossain et al 56 , if 0 < VIF < 5, there is no evidence of multicollinearity.…”
Section: Discussionmentioning
confidence: 99%
“…the processing and marketing of rice 27 . The low experience of farmers of southern Benin in rice production, compared to those of other regions, could be explained by a more recent introduction of rice production in this region 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Sub-Saharan Africa, for example, show that women face several context-related barriers that hinder their participation in entrepreneurship. Specifically, women are deprived of capital resources – land (Adétonah et al , 2015), finance (Chlebicka, 2015; Mandipaka, 2014), cognitive skills (Langevang et al , 2018) and business opportunities – due to restricted social networks (Rutashobya et al , 2009; Spring, 2009). Subsequently, the context influences the characteristics, scale and outcomes of entrepreneurship endeavours and the behaviour of women entrepreneurs (Welter and Smallbone, 2011).…”
Section: Introductionmentioning
confidence: 99%